Growth hormone gene polymorphism in Jaisalmeri and Sindhi camels - JYOTSANA, BASANTI; PRAKASH, VED; SUTHAR, SHALINI; RANJAN, RAKESH (The Indian Journal of Animal Sciences, 2021)
The present study was aimed to assess the genetic polymorphism of growth hormone (GH) gene in Jaisalmeri and Sindhi camels using polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP) technique. Genomic DNA were isolated from venous blood samples collected from 93 Indian camels (Jaisalmeri- 38 and Sindhi-55 camels) and 613-base pair fragment of GH gene was amplified from each genomic DNA sample by polymerase chain reaction. The PCR-RFLP was done using restriction enzyme MspI which revealed three genotypes, viz. CC, CT and TT in both the breeds. Our result indicated that both the breeds were polymorphic in nature. The corresponding genotype frequency in Jaisalmeri and Sindhi breeds were 0.474 and 0.345 for the CC, 0.395 and 0.564 for CT, 0.131 and 0.091 for TT genotypes and the corresponding C allele frequency was 0.671 and 0.627 and T allele frequency was 0.329 and 0.373. The CT genotype was found predominant in the Sindhi breed, whereas CC genotype was predominant in Jaisalmeri breed. The frequency of C allele was higher than the T allele in both of the breeds. These camel populations were in Hardy-Weinberg Equilibrium indicating that the populations meet the HWE assumptions and genetic variations were conserved. It could be concluded that Jaisalmeri and Sindhi camels having different genetic variants of GH gene might be investigated for production a DNA marker for growth and production traits in Indian camels.